Endogenous housing market cycles - Sommervoll, Dag Einar; Borgersen, Trond-Arne; Wennemo, Tom (Journal of Banking & Finance, 2010)
Housing markets tend to display positive serial correlation as well as considerable volatility over time. We present a heterogeneous agent model illustrating the connection between adaptive expectations and housing market fluctuations. A dwelling serves as a shelter, as a vehicle for investment and as mortgage collateral. Interesting dynamics arise as the valuation of these three properties changes over time through the interaction of buyers, sellers and mortgagees. In the absence of credit constraints imposed by mortgagees, house prices oscillate mildly around the equilibrium price. However, credit constraints imposed by mortgagees can affect market dynamics quite dramatically with periods of mild oscillations interrupted by violent collapses. This chaotic behavior arises even though buyers, sellers and mortgagees agree on market forecasts.